ANALISIS PENERAPAN APLIKASI SISTEM INFORMASI PEMERINTAH DAERAH (SIPD) PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA PRABUMULIH - Putri, Feriz Danisya; Tandean, Vivi Adeyani (Journal Accounting International Mount Hope, 2025)
The central government provides an application in delivering information on regional financial management that has been integrated into a network that can connect regional governments with the central government, namely the Regional Government Information System so that information on activity and budget data in regional government financial management can be directly published by the central government. With the SIPD application, regional governments can increase accountability for regional financial management information. This study aims to determine the effectiveness of the implementation of the Regional Government Information System (SIPD) which is reviewed in 3 dimensions, namely goal achievement, integration, and adaptation and to determine the obstacles and strategies in managing obstacles in the SIPD application used by the BPKAD of Prabumulih City. This study uses a descriptive method with a qualitative approach. Data collection techniques used for this study were interviews, observations, and documentation. The results of the study indicate that Prabumulih City has implemented the SIPD application in regional financial management according to Permendagri Number 77 of 2020, but in the resource dimension, especially the indicators on the facilities menu, it is not optimal, there is a lack of understanding of the use of the system and problems related to the SIPD application which often experiences errors. Therefore, it is recommended to conduct intensive training, improve technology infrastructure, and evaluate the system periodically to support the smooth implementation of SIPD in the future.